Implementasi Kegiatan Penyambutan Bulan Suci Ramadhan 1446 H dalam Rangka Meningkatkan Karakter Religius Santriwan/I di Ma’had Al-Mandily - Syaipuddin Ritonga; Muhammad Hatta Lubis; Alfina Nasution; Siti Fatimah; Rezky Fauziah Nur; Nur Adilah Nasution; Novi Rahmadani Sitompul; Tuti Alawiyah; Asrida Lubis; Arobiah Nasution; Muhammad Alwi Batubara; Hidayat Abror (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to describe the collaboration between student of the field PPL from STAIN Mandailing Natal and STAITA Padang Sidempuan in welcoming the holy month of Ramadan 1446 H at MAS Al-Mandily Kampung Padang. The initiative aims to contribute positively to strengthening relationships between educational institutions while introducing religious values to the suurounding communnity. The method used in this study is a participatory approach that involves students and the community of MAS Al-Mandily in every stage of the activity. The result of this study indicate that this collaboration not only improves the quality of religious activities at MAS Al-Mandily, but also provides valuable experience for PPL students in implementing the knowledge they have learned in the field. In addition, the relationship between the two educational institutions will be closer, and have a positive impact on the formation of student character.